TEFSİRİN HEDEF VE SINIRLARI AÇISINDAN KEŞŞAF TEFSİR - Arslan, Gıyasettin (Fırat University, 2017)
Tefsir disiplininde, ortay konan şerh, izah, yorum ve tevillerin gaye ve hedefini bilmek son derece önemlidir. Bu durum aynı zamanda tefsir ilminin sınırlarını da beraberinde gündeme taşımaktadır. Tarihte ve günümüzde pek çok tefsir araştırmacısı diğer branşdaşlarını alanın dışına çıkmak ve hedeften sapmakla itham etmiştir. Bu çalışmada Keşşaf kritiği yapmakla devam edegelen sorunun çözümüne bir nebze katkıda bulunmak istedik

It is very important to know the aim and target of the commentary, explanation, comment and tawils that put forward in the interpretation discipline. This situation also brings the boundary of the interpretation science to agenda. Lots of interpretation researchers have accused the other researchers to comment interpretation out of their main field and distort their target nowadays. In this study, by doing the Keşşaf criticism, we wanted to contribute the solutions of the problems which have lasted
The Keşşaf Interpretation in the Sense of Its Target and Boundaries